DIVERGENSI NUTRISI ANTARA DUA SPESIES SARGASSUM (Phaeophyceae) SIMPATRIK: IMPLIKASI UNTUK APLIKASI PANGAN FUNGSIONAL TERTARGET - Singgih Afifa Putra; Santia Gardenia Widyaswari (Universitas Teuku Umar, 2025)
The industrial application of Sargassum as a functional food ingredient is often limited by a generalized approach that overlooks interspecies biochemical variations. This study addresses current gap through a comparative nutritional analysis of two sympatric species, Sargassum ilicifolium and S. polycystum, collected from the Spermonde Archipelago, Indonesia, to establish a basis for precision bioprospecting. Standardized sample preparation was followed by comprehensive chemical profiling conducted in triplicate (n=3). Proximate and mineral analyses adhered to AOAC protocols, while fatty acid and amino acid profiles were determined using Gas Chromatography-Mass Spectrometry (GC-MS) and Ultra-Performance Liquid Chromatography (UPLC), respectively Comparative data were statistically validated using Independent Samples t-testsResults revealed distinct